Application Of Icp-Oes In The Comparative Analysis Of A Used And Fresh Gasoline Motor Oil (Global Journal of Science Frontier Research, 2012)
In a fresh and 14500 km used oil, viscosity, viscosity index, flash point, pour point, specific gravity, color, total acid number, total base number, water content, as well as concentrations of twenty four elements, were determined. The mineral baesd, gasoline motor oil Speedy SL, from Sepahan Oil Company was chosen for study. The physical properties were characterized by ASTM protocols. The elemental analysis was performed by inductively coupled plasma-optical emission spectroscopy (ICP-OES) . The results indicate that after the application of fresh oil, both of the physical properties and elemental concentrations have been changed significantly. Possible reasons for the observed variations have been discussed.
Keywords: Oil Analysis; ICP-OES; mineral oils; gasoline oil; used oil